Anti-scouring tundish dry material

By adding citroite powder and SiO2 aerogel powder to the dry-closed material, the problems of insufficient strength and poor insulation performance at high temperatures are solved, and the compressive strength and insulation performance are significantly improved, which extends the service life and reduces energy consumption. .

CN119143481AActive Publication Date: 2024-12-17SHANGHAI LIER REFRACTORY MATERIAL +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411260216.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-10
Publication Date
2024-12-17
Estimated Expiration
2044-09-10

AI Technical Summary

Technical Problem

The existing electromelted magnesium sand-phenolic resin-type closure dry-type materials are insufficient at high temperatures, resulting in cracks, deformation and peeling of the material when the molten steel and slag are washed, and the insulation performance is poor, affecting the quality and cost of continuous casting.

Method used

By adding actoli powder and SiO2 aerogel powder, the medium and high temperature strength and insulation properties are improved. Centrolite powder uses its layered structure to form a cross network and chemical bonding to enhance shear and impact resistance; the nanopore structure of SiO2 aerogel powder increases thermal resistance and reflection, and reduces heat conduction and radiation.

Benefits of technology

It significantly improves the medium and high temperature compressive strength and corrosion resistance of the slag dry material, extends the service life, and improves the thermal insulation performance, ensures the temperature stability of the continuous casting process, and reduces energy consumption.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005035332910000101
    Figure BDA0005035332910000101
Patent Text Reader

Abstract

The invention discloses an anti-scouring tundish dry material, and relates to the technical field of tundish refractory materials, and the tundish dry material comprises the following raw material components by mass: 28-32% of 3-1mm fused magnesite, 10-20% of alumina powder, 10-20% of alumina powder, and the balance of alumina powder. The invention relates to an ultra-low thermal conductivity refractory brick which comprises the following components in percentage by weight: 22-30% of 1-0mm fused magnesia, 20-28% of 200-mesh fused magnesia, 3-4.5% of phenolic resin, 1-1.4% of rectorite powder, 0.2-0.3% of SiO2 aerogel powder and the balance of 5-3mm fused magnesia. According to the ultra-low thermal conductivity refractory brick, the special layered structure of the rectorite powder and the ultra-low thermal conductivity of the SiO2 aerogel powder are ingeniously utilized; through the synergistic effect of the two components, the tundish dry material successfully solves the problems of insufficient strength and poor thermal insulation performance on the basis of keeping the original good fire resistance, and the efficiency and economical efficiency of a continuous casting process are remarkably improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of tundish refractory materials, and in particular relates to an anti-scouring tundish dry material. Background Art

[0002] In the modern steel industry, the tundish is an important link between the ladle and the crystallizer during the continuous casting process. The selection of its working lining material directly affects the purity of the molten steel, the continuous casting efficiency and the production cost. As an efficient and environmentally friendly working lining material, the tundish dry material is highly favored due to its convenient construction, rapid curing and good corrosion resistance. In particular, the dry material system with fused magnesia as the main raw material and phenolic resin as the binder has been widely used in the industry due to its excellent refractory properties and suitable chemical stability.

[0003] However, although the fused magnesia-phenolic resin type tundish dry material meets the basic needs of high-temperature working environment to a certain extent, there are still several technical problems that need to be solved in the actual use process. Specifically, it is manifested in: 1. Strength shortcoming: In a specific temperature range, especially around about 1100℃ and 1530℃, this type of dry material shows a significant decrease in strength. The insufficient strength at this stage causes the material to weaken its ability to resist mechanical stress when it encounters severe erosion by molten steel and slag, and it is easy to produce cracks, deformation and even local peeling, which seriously affects the service life of the tundish and the stability of the continuous casting process; 2. Heat loss and erosion are aggravated: Due to the limited thermal insulation performance of the existing dry material, unnecessary heat loss occurs during the transmission process, which not only increases energy consumption, but also may cause uneven temperature of molten steel and affect the quality of continuous casting. At the same time, the erosion effect of molten steel and slag on dry materials at high temperatures is more significant, especially in the temperature range with lower strength, the material's anti-erosion barrier is weak, which further accelerates the damage process of the working lining.

[0004] In view of the above-mentioned technical difficulties, although there have been some targeted improvement measures, such as adjusting the raw material ratio, optimizing the type and dosage of binders, adding specific additives, etc., the existing solutions often cannot take into account the two core requirements of improving medium and high temperature strength and optimizing thermal insulation performance, and while improving one aspect of performance, it may have an adverse effect on other performance. Summary of the invention

[0005] In view of the serious erosion and spalling problems and poor thermal insulation performance of the existing fused magnesia-phenolic resin type dry material caused by insufficient strength during use, the present invention provides an erosion-resistant tundish dry material, which improves the medium and high temperature strength and thermal insulation performance of the dry material by adding rectorite powder and SiO2 aerogel powder.

[0006] The solution adopted by the present invention to solve the technical problem is: an anti-scour tundish dry material, wherein the mass percentage of each raw material component in the tundish dry material is: 3-1mm fused magnesia is 28-32%, 1-0mm fused magnesia is 22-30%, 200-mesh fused magnesia is 20-28%, phenolic resin is 3-4.5%, rectorite powder is 1-1.4%, SiO2 aerogel powder is 0.2-0.3%, and the balance is 5-3mm fused magnesia.

[0007] Furthermore, the tundish dry material comprises 30% 3-1mm fused magnesia, 25% 1-0mm fused magnesia, 24% 200-mesh fused magnesia, 3.5% phenolic resin, 1.2% rectorite powder, 0.3% SiO2 aerogel powder, and the remainder 5-3mm fused magnesia.

[0008] Furthermore, the MgO content in the fused magnesia is ≥91%.

[0009] Furthermore, the rectorite powder has a particle size of 325 mesh and a purity of 98%.

[0010] Furthermore, the specific surface area of ​​the SiO2 aerogel powder is 700-750m 2 / g, bulk density is 40~45kg / m 3 The porosity is 93.5%, the thermal conductivity is 0.012-0.014 W / (m·k), the average particle size is 25 μm, and the surface is hydrophobic.

[0011] Furthermore, when the dry material in the tundish is vibrated and formed, the vibration time of the fetal membrane of the working layer is 120 to 150 seconds.

[0012] Compared with the prior art, the present invention has the following beneficial effects:

[0013] 1. The present invention uses rectorite powder to enhance the medium and high temperature strength and anti-scouring performance of the tundish dry material. Rectorite powder is used as an innovative additive, and its unique layered silicate mineral structure is utilized. This structure has natural interlayer water molecules and exchangeable cations, and can maintain structural stability at high temperatures, while providing good ion exchange and expansion performance. After adding rectorite powder to the dry material of the present invention, its layered structure can form physical and chemical interactions with fused magnesia particles and other components at high temperatures, which is specifically embodied in the following aspects: first, the flaky particles of the rectorite powder can form a cross network inside the dry material, enhance the mechanical bite between the particles, and improve the shear and impact resistance of the material; secondly, the surface active groups of the rectorite powder are chemically bonded with the phenolic resin or other mineral components, thereby enhancing the interface bonding force and improving the integrity of the material; finally, the micro-expansion of the rectorite powder during the heating process helps to fill micro cracks and voids, delay the expansion of cracks at high temperatures, and enhance the crack resistance and toughness of the dry material. Through the above effects, the rectorite powder significantly improves the compressive strength and corrosion resistance of the dry material at medium and high temperature stages, and can effectively prevent the peeling of the dry material caused by the scouring of molten steel and slag.

[0014] 2. The present invention uses SiO2 aerogel powder to improve the thermal insulation performance of dry materials. SiO2 aerogel powder has an extremely low volume density and nanoscale pore structure, which gives it an ultra-low thermal conductivity coefficient and is an ideal high-temperature thermal insulation material. After adding SiO2 aerogel powder in the present invention, the mechanism of modifying and improving the thermal insulation performance of dry materials is specifically reflected in: first, the nanopore structure of the aerogel powder greatly increases the tortuosity of the heat transfer path, significantly increases the thermal resistance when the heat flow passes through the material, and effectively reduces the heat conduction rate; secondly, the nanopores and particles inside the aerogel powder have a strong scattering and reflection effect on thermal radiation, reducing the possibility of thermal radiation directly penetrating the material, and can further reduce heat energy loss; finally, the pores of the aerogel powder can adsorb and store gas to form an efficient thermal insulation layer, prevent convective heat transfer, and can effectively improve the thermal insulation effect. The introduction of SiO2 aerogel powder in the present invention significantly improves the thermal insulation performance of the dry material, effectively suppresses the temperature drop of molten steel, ensures the temperature stability of the continuous casting process, and also reduces the thermal stress caused by temperature fluctuations, indirectly enhancing the overall strength of the dry material.

[0015] The present invention cleverly utilizes the special layered structure of rectorite powder and the ultra-low thermal conductivity of SiO2 aerogel powder, and realizes the performance upgrade of the existing fused magnesia-phenolic resin type tundish dry material through scientific formula design and process optimization. The synergistic effect of the two enables the tundish dry material of the present invention to successfully solve the problems of insufficient strength and poor thermal insulation performance while maintaining the original good refractory performance, thereby significantly improving the efficiency and economy of the continuous casting process. DETAILED DESCRIPTION

[0016] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0017] The present invention provides a technical solution for anti-scouring tundish dry material:

[0018] The invention discloses an anti-scouring tundish dry material, wherein the mass percentage of each raw material component in the tundish dry material is: 28-32% of 3-1mm fused magnesia, 22-30% of 1-0mm fused magnesia, 20-28% of 200-mesh fused magnesia, 3-4.5% of phenolic resin, 1-1.4% of rectorite powder, 0.2-0.3% of SiO2 aerogel powder, and the remainder is 5-3mm fused magnesia.

[0019] The present invention uses rectorite powder as an innovative additive, and utilizes its unique layered silicate mineral structure to play multiple roles in the tundish dry material: on the one hand, the natural interlayer water molecules and exchangeable cations of the rectorite powder keep its structure stable at high temperatures, while providing good ion exchange and expansion properties; on the other hand, its layered structure can form physical and chemical interactions with other components in the dry material at high temperatures, including physical interweaving to form a cross network to enhance the mechanical bite between particles, chemical bonding to enhance the interface bonding force, and thermal expansion to fill micro cracks and gaps to delay crack propagation. Through the above multiple effects, the rectorite powder significantly improves the compressive strength and corrosion resistance of the dry material at medium and high temperature stages, and effectively prevents the peeling of the dry material caused by the scouring of molten steel and slag.

[0020] The present invention significantly enhances the thermal insulation performance of dry materials by introducing SiO2 aerogel powder and utilizing its ultra-low volume density and ultra-low thermal conductivity brought by nano-scale pore structure. The nano-pore structure of SiO2 aerogel powder greatly increases the tortuosity of the heat transfer path, significantly increases the thermal resistance, and effectively slows down the heat conduction. At the same time, the scattering and reflection of thermal radiation by the internal nano-pores and particles reduces the thermal radiation loss. In addition, the adsorption and storage of gas by the pores constructs an efficient thermal insulation layer, blocking the convection heat transfer. These mechanisms work together to not only greatly improve the thermal insulation effect of dry materials, effectively curb the drop in molten steel temperature, and ensure the temperature stability of the continuous casting process, but also indirectly enhance the overall structural strength of dry materials by reducing the thermal stress caused by temperature fluctuations.

[0021] As a preferred embodiment of the present invention, the tundish dry material comprises 30% 3-1mm fused magnesia, 25% 1-0mm fused magnesia, 24% 200-mesh fused magnesia, 3.5% phenolic resin, 1.2% rectorite powder, 0.3% SiO2 aerogel powder, and the remainder 5-3mm fused magnesia.

[0022] The present invention adopts 5-3mm fused magnesia. The fused magnesia particles with larger particle size mainly play a role of skeleton support in the tundish dry material, which can enhance the overall strength and anti-scouring ability of the material, help reduce the shrinkage of the material caused by temperature change during sintering or use, maintain the stability of the material, and the appropriate particle gap can also improve the air permeability of the material, which is beneficial to the flow of molten steel in the tundish and the uniform temperature distribution; 3-1mm fused magnesia is adopted to form a stable skeleton system together with 5-3mm particles. Through reasonable particle size matching, the packing density and uniformity of the dry material can be improved, the porosity can be reduced, and the erosion resistance and anti-scouring property of the dry material can be improved; 1-0mm fused magnesia is adopted Fused magnesia sand, smaller particle size fused magnesia sand can fill the gaps between large particles, can improve the density and compactness of the dry material, and can further improve the thermal shock resistance and erosion resistance of the dry material by refining the particle size distribution. At the same time, small particle size particles of 1-0mm have a larger specific surface area, which is conducive to the diffusion and reaction of materials during sintering and accelerates the sintering process. Using 200 mesh fused magnesia sand, ultra-fine fused magnesia sand particles can significantly refine the microstructure of the material and improve the uniformity and density of the dry material. The refined structure helps to improve the strength, hardness and wear resistance of the dry material, while enhancing the permeability and erosion resistance of the dry material, and can further form a more dense and uniform sintered body.

[0023] As a preferred embodiment of the present invention, the MgO content in the fused magnesia is ≥ 91%.

[0024] The present invention adopts high-purity fused magnesia as raw material. The high-purity fused magnesia has large crystal grains and dense structure during the melting process. The tundish dry material prepared from the high-purity fused magnesia also has good structural stability. The fused magnesia with high MgO content has strong resistance to slag erosion. The prepared tundish dry material can also have good refractoriness and compressive strength, can maintain stable performance in a high temperature environment, and effectively prolongs the service life of the tundish.

[0025] As a preferred embodiment of the present invention, the rectorite powder has a particle size of 325 mesh and a purity of 98%.

[0026] The invention adopts high-purity and fine-grained rectorite powder, which helps to reduce the thermal conductivity of the dry material, thereby improving its thermal insulation performance, helping to reduce the temperature loss of molten steel in the tundish, and improving the continuous casting production efficiency; during the sintering process, the fine rectorite powder particles can react with other components more quickly, promoting material transfer and densification during the sintering process, which helps to form a more uniform and dense sintered body, and improves the overall performance of the tundish dry material.

[0027] As a preferred embodiment of the present invention, the specific surface area of ​​the SiO2 aerogel powder is 700-750m 2 / g, bulk density is 40~45kg / m 3 The porosity is 93.5%, the thermal conductivity is 0.012-0.014 W / (m·k), the average particle size is 25 μm, and the surface is hydrophobic.

[0028] The present invention uses SiO2 aerogel powder with a high specific surface area, which can more effectively adsorb and fix other components in the intermediate bag dry material, thereby improving the uniformity and stability of the overall material; the low bulk density enables the SiO2 aerogel powder to significantly reduce the overall weight of the material when preparing the intermediate bag dry material. While maintaining the same volume, the material with a low bulk density can fill more space, thereby improving the filling rate and density of the intermediate bag dry material; the high porosity enables the SiO2 aerogel powder to have an extremely low thermal conductivity, which can effectively reduce the transfer of heat, improve the thermal insulation performance of the intermediate bag dry material, and reduce heat loss At the same time, the appropriate pore structure helps to improve the air permeability of the material, reduce the pressure difference caused by gas accumulation, and improve the stability and service life of the material; low thermal conductivity can significantly reduce the heat transfer rate in the material, improve the thermal insulation effect of the dry material in the tundish, protect the temperature of the molten steel, reduce energy consumption, and effectively improve the thermal insulation performance of the dry material; smaller particle size helps to fill the tiny gaps in the material and improve the density and strength of the material; after the SiO2 aerogel powder is hydrophobically modified, the hydrophobic surface can reduce the heat transfer through the interface, thereby reducing the thermal bridge effect, which helps to improve the thermal insulation performance of the dry material in the tundish.

[0029] As a preferred embodiment of the present invention, when the dry material in the tundish is vibrated and formed, the vibration time of the fetal membrane of the working layer is 120 to 150 seconds.

[0030] The vibration time of the fetal membrane of the working layer of the present invention is 120 to 150 seconds, which helps to reduce the gaps between particles and improve the density of the material, thereby enhancing the overall strength and corrosion resistance of the working layer, improving the material structure, improving the construction efficiency and meeting the process requirements.

[0031] Specific implementation cases:

[0032] A specific embodiment of the anti-scour tundish dry material of the present invention is provided below.

[0033] Embodiment 1:

[0034] The present embodiment provides an anti-scour tundish dry material, wherein the mass percentage of each component of the tundish dry material is: 30% of 3-1mm fused magnesia, 25% of 1-0mm fused magnesia, 24% of 200-mesh fused magnesia, 3.5% of phenolic resin, 1.2% of rectorite powder, 0.3% of SiO2 aerogel powder, and the remainder is 5-3mm fused magnesia.

[0035] Embodiment 2:

[0036] The present embodiment provides an anti-scour tundish dry material, wherein the mass percentage of each component of the tundish dry material is: 29% of 3-1mm fused magnesia, 28% of 1-0mm fused magnesia, 23% of 200-mesh fused magnesia, 3.9% of phenolic resin, 1.3% of rectorite powder, 0.2% of SiO2 aerogel powder, and the remainder is 5-3mm fused magnesia.

[0037] Embodiment 3:

[0038] The present embodiment provides an anti-scour tundish dry material, wherein the tundish dry material has the following components in percentage by mass: 28% 3-1 mm fused magnesia, 22% 1-0 mm fused magnesia, 28% 200 mesh fused magnesia, 4.5% phenolic resin, 1.4% rectorite powder, 0.2% SiO2 aerogel powder, and the remainder 5-3 mm fused magnesia.

[0039] Embodiment 4:

[0040] The present embodiment provides an anti-scour tundish dry material, wherein the mass percentage of each component of the tundish dry material is: 31% of 3-1mm fused magnesia, 26.5% of 1-0mm fused magnesia, 20% of 200-mesh fused magnesia, 4.2% of phenolic resin, 1% of rectorite powder, 0.3% of SiO2 aerogel powder, and the remainder is 5-3mm fused magnesia.

[0041] Embodiment 5:

[0042] The present embodiment provides an anti-scour tundish dry material, wherein the mass percentage of each component of the tundish dry material is: 32% of 3-1mm fused magnesia, 30% of 1-0mm fused magnesia, 22% of 200-mesh fused magnesia, 3% of phenolic resin, 1.1% of rectorite powder, 0.2% of SiO2 aerogel powder, and the remainder is 5-3mm fused magnesia.

[0043] Embodiment 6:

[0044] The present embodiment provides an anti-scour tundish dry material, wherein the mass percentage of each component of the tundish dry material is: 30% of 3-1mm fused magnesia, 27% of 1-0mm fused magnesia, 25% of 200-mesh fused magnesia, 4% of phenolic resin, 1.2% of rectorite powder, 0.3% of SiO2 aerogel powder, and the remainder is 5-3mm fused magnesia.

[0045] Comparative Example 1:

[0046] This comparative example provides an anti-scour tundish dry material. The tundish dry material has the following components in percentage by mass: 29% 3-1mm fused magnesia, 28% 1-0mm fused magnesia, 23% 200-mesh fused magnesia, 3.9% phenolic resin, 0.2% SiO2 aerogel powder, and the remainder 5-3mm fused magnesia. This comparative example does not contain rectorite powder.

[0047] Comparative Example 2:

[0048] This comparative example provides an anti-scour tundish dry material. The mass percentage of each component of the tundish dry material is: 28% of 3-1mm fused magnesia, 22% of 1-0mm fused magnesia, 28% of 200-mesh fused magnesia, 4.5% of phenolic resin, 1.4% of rectorite powder, and the remainder is 5-3mm fused magnesia. This comparative example does not contain SiO2 aerogel powder.

[0049] Comparative Example 3:

[0050] This comparative example provides an anti-scour tundish dry material. The mass percentage of each component of the tundish dry material is as follows: 31% of 3-1mm fused magnesia, 26.5% of 1-0mm fused magnesia, 20% of 200-mesh fused magnesia, 2% of phenolic resin, 1% of rectorite powder, 0.3% of SiO2 aerogel powder, and the remainder is 5-3mm fused magnesia. The content of phenolic resin in this comparative example is relatively low, only 2%.

[0051] Comparative Example 4:

[0052] This comparative example provides an anti-scour tundish dry material. The mass percentage of each component of the tundish dry material is as follows: 32% of 3-1mm fused magnesia, 30% of 1-0mm fused magnesia, 32% of 200-mesh fused magnesia, 3% of phenolic resin, 1.1% of rectorite powder, 0.2% of SiO2 aerogel powder, and the remainder is 5-3mm fused magnesia. In this comparative example, the content of 200-mesh fused magnesia is as high as 32%.

[0053] The present invention uses a kind of anti-scour tundish dry material of Examples 1 to 6 and Comparative Examples 1 to 4, and prepares the sample strip according to GB / T4513.5-2017 "Amorphous Refractory Materials Part 5: Sample Preparation and Pretreatment", and the test of flexural strength and compressive strength is carried out according to the test method in GB / T 4513.6-2017 "Amorphous Refractory Materials Part 6: Determination of Physical Properties", and the cladding temperature is measured by an infrared temperature measuring gun. The tests of Examples 1 to 6 and Comparative Examples 1 to 4 are all carried out using the same new permanent layer "rectangular" tundish, and the location and time of the cladding temperature test are the same. The erosion rate is calculated by measuring the residual thickness of the dry material after offline. The test results are shown in Table 1:

[0054] Table 1 Test results of Examples 1 to 6 and Comparative Examples 1 to 4

[0055]

[0056] Comparative Example 1 is based on Example 2, but the addition of rectorite powder is cancelled, and 5-3 mm fused magnesia is correspondingly increased. As can be seen from Table 1, compared with Example 2, the flexural strength and compressive strength of Comparative Example 1 are significantly reduced, and the erosion rate is also increased to 2.14 mm / h, which is significantly lower than the test effect of Example 2.

[0057] Comparative Example 2 is based on Example 3, but the addition of SiO2 aerogel powder is cancelled, and 5-3mm fused magnesia is correspondingly added. As can be seen from Table 1, compared with Example 3, the cladding temperature of the slag line and the bottom of the cladding in the impact zone and the slag line and the bottom of the cladding in the buffer zone in Comparative Example 2 is significantly increased, and the cladding temperature rise range is 17-20°C. The erosion rate is also slightly increased to 1.51mm / h, which is significantly lower than the test effect of Example 3.

[0058] Comparative Example 3 is based on Example 4, reducing the addition of phenolic resin and correspondingly increasing 5-3mm fused magnesia. As can be seen from Table 1, compared with Example 4, the flexural strength and compressive strength of Comparative Example 3 are significantly reduced, and the erosion rate is also increased to 1.78mm / h, which is significantly lower than the test effect of Example 4.

[0059] Comparative Example 4 is based on Example 5, with the addition of 200-mesh fused magnesia increased and the fused magnesia of 5-3 mm reduced accordingly. As can be seen from Table 1, compared with Example 5, the cladding temperature of the slag line and the bottom of the impact zone, the slag line and the bottom of the buffer zone is slightly increased, and the erosion rate is also increased to 1.66 mm / h, which is significantly lower than the test effect of Example 5.

[0060] In summary, adding rectorite powder can effectively improve the flexural strength and compressive strength of the dry material in the tundish, and adding SiO2 aerogel powder can significantly enhance the thermal insulation performance of the dry material in the tundish. At the same time, each raw material needs to be designed through a scientific formula, and through the synergistic effect of each other, the flexural strength, compressive strength and thermal insulation performance can be effectively improved while ensuring the original refractoriness.

[0061] The above description is only a preferred embodiment of the present invention and does not limit the present invention. Any modifications, equivalent substitutions and improvements made within the spirit and principle of the present invention should be included in the protection scope of the present invention.

Claims

1. An anti-scour tundish dry material, Features: The mass percentage of each raw material component in the tundish dry material is: 3-1mm fused magnesia is 28-32%, 1-0mm fused magnesia is 22-30%, 200 mesh fused magnesia is 20-28%, phenolic resin is 3-4.5%, rectorite powder is 1-1.4%, SiO 2 The aerogel powder is 0.2-0.3% of fused magnesia with the remainder being 5-3mm.

2. The anti-scour tundish dry material according to claim 1, Features: The dry material of the tundish contains 30% 3-1mm fused magnesia, 25% 1-0mm fused magnesia, 24% 200-mesh fused magnesia, 3.5% phenolic resin, 1.2% rectorite powder, and 1% SiO 2 The aerogel powder is 0.3% and the balance is 5-3mm fused magnesia.

3. The anti-scour tundish dry material according to claim 1, Features: The MgO content in the fused magnesia is ≥91%.

4. The anti-scour tundish dry material according to claim 1, Features: The rectorite powder has a particle size of 325 meshes and a purity of 98%.

5. The anti-scour tundish dry material according to claim 1, Features: The SiO 2 The specific surface area of ​​aerogel powder is 700~750m 2 / g, bulk density is 40~45kg / m 3 The porosity is 93.5%, the thermal conductivity is 0.012-0.014 W / (m·k), the average particle size is 25 μm, and the surface is hydrophobic.

6. The anti-scour tundish dry material according to claim 1, Features: When the dry material in the tundish is vibrated and formed, the vibration time of the fetal membrane of the working layer is 120 to 150 seconds.

Citation Information

Patent Citations

  • Sodium modified rectorite clay

    CN103979556A

  • Lightweight ceramsite with rectorite and through holes

    CN105884334A

  • Gravel-shaped lightweight rectorite ceramisite with air purifying function

    CN106431310A

  • Phenolic resin for carbon-containing refractory material and preparing method of phenolic resin

    CN107540804A

  • Magnesia-spinel-carbon basic refractory

    KR1020050064557A